Evolution of Apathy in Early Parkinson's Disease: A 4-Years Prospective Cohort Study - Ou, Ruwei; Lin, Junyu; Liu, Kuncheng; Jiang, Zheng; Wei, Qianqian; Hou, Yanbing; Zhang, Lingyu; Cao, Bei; Zhao, Bi; Song, Wei; Shang, Huifang (Frontiers in Aging Neuroscience, 2021)
Objective: We investigated the prevalence, evolution, associated factors, and risk factors of apathy in a cohort of patients with early-stage Parkinson’s disease (PD), who underwent 4-year prospective follow-up. Methods: This study included 188 patients with PD (baseline disease duration < 3 years), who underwent an annual evaluation using the Lille Apathy Rating Scale (LARS). Based on the cut-off value of -21 observed on the LARS, patients were categorized as PD with and without apathy. The generalized estimating equations model was utilized to determine the factors associated with apathy, and the Cox proportional hazards regression model was used to determine the predictors of apathy. Results: Apathy increased from a baseline rate of 18.6% to 28.8% after 4 years; notably, this rate was not persistent across patients’ visits. The LARS score was independently associated with male sex (B 8.131, P = 0.009), low Frontal Assessment Battery scores (B 0.567, P = 0.011), low attention scores on the Montreal Cognitive Assessment test (B 0.217, P = 0.026), high Hamilton Depression Rating Scale (HDRS) scores (B 1.362, P < 0.001), high Unified Parkinson’s Disease Rating Scale part III scores (B 1.147, P < 0.001), and prolonged follow-up time (B 1.785, P = 0.048). A high HDRS score was the only predictor of apathy in PD (hazard ratio [HR] 1.043, P = 0.026). Conclusions: The risk of apathy is higher in men with progressive PD accompanied by disease-specific motor and non-motor symptoms. Depression during early-stage PD is a primary risk factor for apathy in PD.